(untitled) (Scientific journal of the Fergana State University, 2025)
The structural state of the cohesive soil is provided by favorable water and air, and, consequently, thermal, biological and nutritional regimes, i.e. create the best conditions for soil fertility. The quality of pre-sowing treatments is determined by the degree of soil crumbling. It is known that pre-sowing cultivation tools must ensure good crumbling of the soil throughout the cultivated layer.